Armed robbery in Australia 2009–10: National Armed Robbery Monitoring Program report - Georgina Fuller
This report summarises key findings from information describing the 12,005 victims of armed robbery reported to police in Australia during the 2009 and 2010 calendar years Abstract: The Australian Institute of Criminology’s National Armed Robbery Monitoring Program (NARMP) has been recording and reporting on trends in armed robbery since 2003. It is the only national dataset detailing armed robbery in Australia. This report is the first released after NARMP moved to biennial reporting and it summarises key findings from information describing the 12,005 victims reported to police in Australia during the 2009 and 2010 calendar years